2012
DOI: 10.1159/000342104
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Ipsilateral Renal Ureteral Calculi by Combining Retroperitoneal Laparoscopic Surgery with Tubeless Mini-Percutaneous Nephrolithotomy

Abstract: Objectives: To report and discuss the role of the treatment of ipsilateral renal and upper middle ureteral stones in patients by combing retroperitoneal laparoscopic surgery with tubeless mini-percutaneous nephrolithotomy. Patients and Methods: Eleven patients associated with ipsilateral renal and upper middle ureteral stones underwent combing retroperitoneal laparoscopic surgery with tubeless mini-percutaneous nephrolithotomy after failure of shockwave or ureteroscopy lithotripsy. Their data were analyzed ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…The incidence of Ureteral calculi in men is higher than that in women. To date, drugs, ESWL, ureteroscopy, percutaneous nephroscope lithotripsy and laparoscope are main therapies for ureteral stone [27][28][29] . However, the selection of treatment for ureteric stones remains a discussed topic in urology.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of Ureteral calculi in men is higher than that in women. To date, drugs, ESWL, ureteroscopy, percutaneous nephroscope lithotripsy and laparoscope are main therapies for ureteral stone [27][28][29] . However, the selection of treatment for ureteric stones remains a discussed topic in urology.…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in hemoglobin during mini-ECIRS and mini-PCNL was significantly lower than that with conventional-PCNL [36]. Sun and Peng [37] also reported that, in carefully selected patients, combining retroperitoneal laparoscopic surgery with tubeless mini-PCNL could treat ipsilateral renal and upper middle ureteral calculi with the advantages of high SFR and less complications. Therefore, mini-PCNL combined with certain technologies might be a better choice for stones in the lower calyx.…”
Section: Discussionmentioning
confidence: 99%
“…Since 30% of asymptomatic stones eventually become symptomatic 4 , many urologists routinely treat patients with multiple ipsilateral stones under a single anesthetic. [5][6][7][8][9][10] As ureteroscopy is generally well tolerated and associated with a low complication rate many advocate a single session for treating bilateral stones as well. [11][12][13][14][15][16] Recent studies examining ureteroscopy for multiple ipsilateral stones (I-URS) suggest this approach to be associated with longer procedure times, higher ureteric stent placement rates, and a longer stent dwell time.…”
Section: Introductionmentioning
confidence: 99%